ISOLATED RUPTURES OF THE SUPRASPINATUS MUSCLE - Holibka, Radomir; Ditmar, Rudolf; Holibkova, Alzbeta; Laichman, Stanislav; Ruzickova, Katherine (Biomedical papers, 2003)
We rarely encounter isolated ruptures of the supraspinatus muscle. At the Clinic of Orthopedics at the Faculty Hospital in Olomouc, we encountered only 21 cases out of 385 arthroscopic operation cases from October 1998 to October 2003. The patients were examined by USG, 5 patients were examined arthrographically and 3 patients underwent MRI examination. Of these 21 patients, only 3 were operated for acute post-injury haemarthrosis of the shoulder joint. During arthroscopic operation, an isolated rupture of the supraspinatus muscle was discovered in all these patients. The remaining 40 patients were only treated at our clinic for problems associated with impingement syndrome after an interval of 3-11 months and were indicated for operational therapy for the rupture of the supra-spinatus muscle, verified sonographically and by MRI. Surgically we performed end to end sutures in 12 patients, in 9 cases we performed refixation using 1-2 titanium MITEK anchors. We supplemented the work by a detailed anatomical study of the supraspinatus muscle on 27 cadaverous anatomical preparations. It was noted that the supraspinatus muscle may be divided into three parts, with a superficial and deep layer of muscle fascicles. An aponeurotic insertion tendon runs through the center, to which part of the superficial muscle fascicles are attached. The muscle fascicles, including the central attachment tendon, run across the superior margin of the shoulder joint and by broad tendon are attached to the superior surface of the greater tubercle of the humerus. Together with the long head of the biceps muscle, they act as a significant shoulder stabiliser. The authors believe that due to the course of the muscle fascicles, this muscle acts as a significant shoulder stabiliser and a powerful abductor and elevator in the shoulder joint. The inferior portion of the muscle fascicles acts as an external rotator of the shoulder.
Keywords: Supraspinatus muscle / Arthroscopy / Muscle ruptures / Surgical therapy / Muscle structure